Gastrointestinal stromal tumor metastasis to the ovary: A case report. (April 2021) - Yamaguchi, Takahisa; Kinoshita, Jun; Saito, Hiroto; Shimada, Mari; Terai, Shiro; Moriyama, Hideki; Okamoto, Koichi; Nakamura, Keishi; Tajima, Hidehiro; Ninomiya, Itasu; Mizuno, Yasutsugu; Nakada, Satoko; et al.
Gastrointestinal stromal tumors are common mesenchymal tumors of the gastrointestinal tract. The major site of metastasis for gastrointestinal stromal tumors is the liver or peritoneum, while metastasis to the ovary is exceptionally rare. A 53-year-old woman visited the hospital for bloating and anorexia and was diagnosed with a huge gastric gastrointestinal stromal tumor and peritoneal metastasis in the pelvis on upper gastrointestinal endoscopy and abdominal enhanced computed tomography. After administration of imatinib, the tumor was significantly reduced, and we performed laparoscopic pelvic tumor resection and open proximal gastrectomy with transverse colectomy. Intraoperatively, the pelvic tumor was found to be an ovarian tumor. Microscopic examination confirmed a gastric gastrointestinal stromal tumor with ovarian metastasis. In conclusion, we experienced a rare case of gastric gastrointestinal stromal tumor with ovarian metastasis. Preoperative administration of imatinib was successful and radical resection was achieved. Although pelvic tumors are difficult to differentiate preoperatively, the possibility of ovarian metastasis from gastrointestinal stromal tumor should be considered.